2013
DOI: 10.1007/s10640-013-9751-y
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Pure Time Effect From Site and Preference Heterogeneity Effects in Benefit Transfer: An Empirical Investigation of Transferability

Abstract: Two identical open-ended contingent valuation surveys assessing willingness-topay for better protection against flooding were administered in 2005 and 2010 at the same site. The 2010 survey was administered to the same respondents as those interviewed in 2005 as well as to new participants. This experimental design allows us to separate the pure temporal dimension from the spatial and social dimensions of transferability, thereby permitting an investigation of the temporal reliability associated with a transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The stability of valuation functions and WTP estimates across time needed in order to undertake value transfer exercises has been the focus of some of the above-mentioned studies as well as others. The robustness of the coefficient estimates within functions from past stated preference studies is a key consideration if they are destined for use in value transfer ( Brouwer, 2006 ; Fetene et al, 2014 ; Hynes et al, 2018 ). Ji et al (2020) were concerned with the temporal reliability of welfare estimates for use in value transfer but from the perspective of revealed preference data.…”
Section: The Stability Of Valuation Functions and Wtp Estimatesmentioning
confidence: 99%
“…The stability of valuation functions and WTP estimates across time needed in order to undertake value transfer exercises has been the focus of some of the above-mentioned studies as well as others. The robustness of the coefficient estimates within functions from past stated preference studies is a key consideration if they are destined for use in value transfer ( Brouwer, 2006 ; Fetene et al, 2014 ; Hynes et al, 2018 ). Ji et al (2020) were concerned with the temporal reliability of welfare estimates for use in value transfer but from the perspective of revealed preference data.…”
Section: The Stability Of Valuation Functions and Wtp Estimatesmentioning
confidence: 99%
“…Tests of intertemporal choice consistency have appeared periodically in the CV literature since the late 1990s (see McConnell et al 1998;Jorgensen et al 2004;Brouwer and Bateman 2005;Brouwer 2006;Fetene et al 2104). Within the DCE literature, there areonly a few examples of the same respondents completing identical sets at different points in time 1 .…”
Section: Information Effects and Intertemporal Choice Consistencymentioning
confidence: 99%
“…As it is common for the source study and benefit transfer applications to take place several years apart, it is at least implicitly assumed that underlying preferences are temporally stable (Brouwer 2006) and choices are consistent (Schaafsma et al 2014). The validity and reliability of these assumptions have been tested in different ways and over different time periods in SP studies, varying from just a few weeks or months to several years, using either the same B Roy Brouwer rbrouwer@uwaterloo.ca 1 or different samples (e.g., Whitehead and Hoban 1999;Berrens et al 2000;Brouwer and Bateman 2005;Brouwer 2012;Fetene et al 2014). Based on an overview of the existing test-retest contingent valuation (CV) literature, McConnell et al (1998) concluded that SP and corresponding willingness to pay (WTP) values are stable over a time period of two years.…”
Section: Introductionmentioning
confidence: 99%